TATA KELOLA KOLABORASI MELALUI SEGORO BENING DAN CETING BUHARI DALAM PENANGANAN KASUS STUNTING DI YOGYAKARTA - Driatama, Dyas Ayuda (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2024)
The research aims to determine the dominant factors determining stunting, the collaborative governance carried out by the Yogyakarta City Government in dealing with stunting, and community participation in the form of community movements formed in handling stunting in the City of Yogyakarta. The research method used is qualitative. The data collection techniques used in this research are documentation and interviews. The results of this research explain that stunting is one of the unsolved problems in the city of Yogyakarta. This is because there are still high cases of stunting in several Islamic boarding school areas in Yogyakarta City. The dominant factors determining stunting are pregnant women with CED (Chronic Energy Deficiency) and smoking. The collaborative governance of the Yogyakarta City Government or in this case the Yogyakarta City Health Service has collaborated with various parties from the government sector, academic sector, business sector and civil society sector. These sectors are involved in handling stunting in the form of innovative community movements, namely the Segoro Bening community movement (Spirit of Mutual Cooperation Free from Stunting) which was spearheaded by the Wirobrajan Ministry of Education and Ceting Buhari (Prevent Stunting for 1000 Days) which was spearheaded by the Gedongtengen Ministry of Education. Apart from the community movement, the Yogyakarta City Government has also formed a TPPS (Team for the Acceleration of Stunting Reduction) which holds discussion sessions every two weeks between several related agencies. Even so, there are still several obstacles in handling this. The obstacles in question are that sometimes people are not disciplined in following directions from the Yogyakarta City Health Service, as well as misunderstandings in communication in implementation in the field in handling stunting.